2019
DOI: 10.1111/ipd.12467
|View full text |Cite
|
Sign up to set email alerts
|

RANKL is associated with persistent primary teeth and delayed permanent tooth emergence

Abstract: Background Tooth eruption is a process that is not fully understood. Aim To evaluate whether genetic polymorphisms for RANK/RANKL/OPG are associated with delayed tooth emergence. To evaluate whether the relative expression of this genes is associated with persistent primary teeth. Design To evaluate whether genetic polymorphisms for RANK/RANKL/OPG could be involved in delayed tooth emergence, saliva samples from 160 children, aged 6‐13 years old, were analysed. To test if there is correlation between gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…The authors identified that a total of 51 different variations of the PTH1R (parathyroid hormone 1 receptor) gene were associated with the primary failure of eruption [ 12 ]. More recently, some studies have also raised the suggestion that the mild forms of tooth eruption alterations, such as delayed tooth eruption with or without PPT, also have a genetic background involved in its etiology [ 4 , 13 , 14 , 15 ]. Variations (SNPs) in genes such as the receptor activator of NF-κB ligand (RANKL) [ 13 ] and Matrix metalloproteases 8 (MMP8) [ 14 ] could be involved in this common condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors identified that a total of 51 different variations of the PTH1R (parathyroid hormone 1 receptor) gene were associated with the primary failure of eruption [ 12 ]. More recently, some studies have also raised the suggestion that the mild forms of tooth eruption alterations, such as delayed tooth eruption with or without PPT, also have a genetic background involved in its etiology [ 4 , 13 , 14 , 15 ]. Variations (SNPs) in genes such as the receptor activator of NF-κB ligand (RANKL) [ 13 ] and Matrix metalloproteases 8 (MMP8) [ 14 ] could be involved in this common condition.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, some studies have also raised the suggestion that the mild forms of tooth eruption alterations, such as delayed tooth eruption with or without PPT, also have a genetic background involved in its etiology [ 4 , 13 , 14 , 15 ]. Variations (SNPs) in genes such as the receptor activator of NF-κB ligand (RANKL) [ 13 ] and Matrix metalloproteases 8 (MMP8) [ 14 ] could be involved in this common condition. Since all cases of tooth agenesis (excluding third molars agenesis) were excluded from our study, it is worth mentioning that all PPT cases also present with the delayed permanent tooth eruption of its successor.…”
Section: Discussionmentioning
confidence: 99%
“…DTE is the most encountered deviation from normal eruption. 68 Gaucher disease, glycogen storage disorder types 1a and 1b, I-cell disease (mucolipidosis II), mucopolysaccharidoses (predominantly Hurler Scheie, Hunter and Maroteaux Lamy syndrome) 25,69 portray systemic conditions with a predilection for DTE. Moreover, local factors such as cleft lip and palate, bony pathology, and supernumerary teeth that occur as part of certain IEM have a possibility to cause a localised DTE.…”
Section: Considerations In the Dental Management Of Metabolic Disordersmentioning
confidence: 99%
“…Delayed tooth eruption (DTE) describes a statistically significant delayed eruption of a tooth (or teeth) compared to predefined norms for age, sex, and ethnicity. DTE is the most encountered deviation from normal eruption 68 . Gaucher disease, glycogen storage disorder types 1a and 1b, I‐cell disease (mucolipidosis II), mucopolysaccharidoses (predominantly Hurler Scheie, Hunter and Maroteaux Lamy syndrome) 25,69 portray systemic conditions with a predilection for DTE.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of ectopic eruption is 15.70%, its timely diagnosis is essential to plan a timely and effective treatment and thus avoid damage to the occlusion and costly orthodontic treatments. Arid, J, (2019). The teeth that have a predilection for erupting ectopically are the permanent third molars, followed by the maxillary canines and first molars constituting 0.8 to 2.8%.…”
mentioning
confidence: 99%